Illuminated postcards, image of the frivolous. Influence of the French theater in the Spanish stages of the early twentieth century - Oñoro Barba, Susana (Revista General de Información y Documentación, 2025)
Illuminated cupletistas postcards in fin-de-siecle Spain represent a singular phenomenon with the production of millions of copies distributed within and across borders. Eclipsed by the normalization of black and white photography officially accepted as “artistic photography” and relegated to oblivion by social morality, the colored cupletistas postcards exercised an essential social function in the impulse of the process of change that the Spanish society was living in between centuries. After identifying the extensive production of cupletists' postcards that constituted the major channel of economic income of the Spanish photographic studios at the beginning of the century, we first analyze the causes of the generalized use of rudimentary techniques of color application on the positive black and white image, to the detriment of other more sophisticated and innovative techniques such as photochrome. This leads us to analyze the social and cultural context in which the photographic document develops and the social function acquired by the cupletistas postcard to understand that the use of this rudimentary technique responds to the need for an agile and economical process that facilitates mass production, as well as the intentionality of a creative process closer to the “artistic intervention” than to the mere application of color. This intention interferes with and modifies the narrative of the cupletistas postcard and reinforces its use as a tool for the promotion of the modernization process that fin-de-siecle Spain was undergoing.
Keywords: Photography; postcard; intervened photography; cupletista; fin-de-siecle Spain; Spanish dance